2022
DOI: 10.1002/asia.202200465
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐free, B(C6F5)3‐Catalyzed S−H Insertion of Thiophenols and Thiols with α‐Diazoesters

Abstract: Described herein is a B(C 6 F 5 ) 3 -catalyzed SÀ H insertion reaction of thiophenols and thiols with α-diazoesters to access valuable α-thioesters. With the established protocol, an array of α-thioester products are generated in moderate to good yields with broad scope and functional group tolerance. In addition, this reaction maintains its high efficiency on gram scale and the product can be easily transformed into other useful motifs. This reaction proceeds under solvent-free conditions at room temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Related insertion into O-H bonds has been demonstrated by the groups of Tang 14 and Jiang 15 affording routes to α-hydroxyesters and α-phosphoryloxy carbonyl compounds, respectively. Li and coworkers 16 described related insertions into S-H bonds, while He and Koenig described analogous insertions in N-H and C-H bonds affording alkylations of car-bazole derivatives, 17 while we reported the N-alkylations of triazole 18 and 2-hydroxybenzo-thiazoles. 19 Related derivatizations of diazomethanes with azide, 20 and carbonate 21 have also been reported.…”
mentioning
confidence: 69%
“…Related insertion into O-H bonds has been demonstrated by the groups of Tang 14 and Jiang 15 affording routes to α-hydroxyesters and α-phosphoryloxy carbonyl compounds, respectively. Li and coworkers 16 described related insertions into S-H bonds, while He and Koenig described analogous insertions in N-H and C-H bonds affording alkylations of car-bazole derivatives, 17 while we reported the N-alkylations of triazole 18 and 2-hydroxybenzo-thiazoles. 19 Related derivatizations of diazomethanes with azide, 20 and carbonate 21 have also been reported.…”
mentioning
confidence: 69%
“…The binding sites of the borane with the diazo compound and the mode of N 2 release are also discussed. We have catalogued the reactions by reaction type including O-H, 10 N-H, 11,12 S-H, 13 and C-H insertions, 14,15 azide insertion, 16 carbonate transfer, 17 C-C and C=C bond-forming reactions, 18,19 cascade reactions, 20,21 and annulation reactions, 22,23 by utilizing diazo compounds as a carbene synthon in the presence of the borane B(C 6 F 5 ) 3 as a metal-free catalyst.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Li and co-workers have shown that the neat mixing of thiols with -aryl--diazo esters produced the -thio ester as a product (Scheme 6). 13 Various thiols including thiophenol, thiophene-3-thiol, and propene-1-thiol effectively participated in the S-H insertion reaction to yield the desired -thio ester derivatives as shown in Scheme 6. It is predicted that the formation of the reactive carbene intermediate is expected to be involved to promote the addition reaction with thiols followed by proton transfer to afford the final product.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Light-induced reactions of diazo compound become crucial in organic synthesis and drug discovery, [1][2][3][4] facilitating new transformations and opening up unexplored chemical space for the biologically active molecule. 5 Highly reactive diazo compounds can undergo various chemical transformation including C-H, 6 O-H, 7 Si-H, 8,9 N-H, 10,11 S-H bonds insertion, 12,13 Wolff rearranged product formation, 14 cyclopropanation, 15,16 cyclopropenation, 17 cycloaddition reaction 17,18 etc. In the early phases of research, thermal-assisted conditions were commonly used to generate carbenes.…”
Section: Introductionmentioning
confidence: 99%